2008
DOI: 10.1002/pssb.200844203
|View full text |Cite
|
Sign up to set email alerts
|

The electric‐field effect on the exciton photoconductivity and Urbach tail in GaSe crystals

Abstract: The direct free exciton (n = 1) photoconductivity in GaSe crystals has been investigated as a function of applied electric field. The changes observed in the exciton photoconductivity have been analyzed using the Franz–Keldysh, exciton electroabsorption, and Frenkel thermoelectric‐field effects. The intensity of exciton photoconductivity peak was found to increase exponentially with the applied field. The exciton peaks broaden as the magnitude of applied field is increased and shift to lower energies with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As seen from the analyses, these peaks shift to longer wavelengths with the square root of applied field consistent with the Pool-Frenkel thermoelectric field effect. In a previous study, we have shown that the exciton photoconductivity varied with applied field according to the Pool-Frenkel thermoelectric field effect [13]. In that study, the contribution of excitons to the increase in photoconductivity was explained by the thermoelectric field ionization of excitons to free charge carriers.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…As seen from the analyses, these peaks shift to longer wavelengths with the square root of applied field consistent with the Pool-Frenkel thermoelectric field effect. In a previous study, we have shown that the exciton photoconductivity varied with applied field according to the Pool-Frenkel thermoelectric field effect [13]. In that study, the contribution of excitons to the increase in photoconductivity was explained by the thermoelectric field ionization of excitons to free charge carriers.…”
Section: Resultsmentioning
confidence: 96%
“…Excitonic effects are important in the optic absorption, electrophotoluminescence and photoconductivity of GaSe crystals, which are members of layered A III B VI crystal family, and these effects have been investigated widely [1,[13][14][15][16][17][18][19]. Unlike other crystals, exciton states continue to exist at room temperature and above in GaSe crystals [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation